2013
DOI: 10.1161/circulationaha.112.001099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Persistent Left Bundle-Branch Block After Transcatheter Aortic Valve Implantation With CoreValve Revalving System

Abstract: Background-Conduction. Survival analyses and inherent log-rank tests showed that LBBB was not associated with higher all-cause mortality, cardiac mortality, or hospitalization for heart failure at 30 days or 1 year. At 30 days, but not at 1 year, group A had a significantly higher rate of pacemaker implantation. Conclusions-In this registry of high-volume centers, persistent LBBB after CoreValve Revalving System transcatheter aortic valve implantation showed no effect on hard end points. On the other hand, LBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 27 publications
6
77
2
2
Order By: Relevance
“…The diagnosis criteria for LBBB were based on the recommendations from the American Heart Association/American College of Cardiology Foundation/Heart Rhythm Society 20 in 4 studies 3,4,13,18 and from the World Health Organizational/International Society and Federation for Cardiology 21 in 2 studies. 11,19 One study 12 did not detail the diagnosis criteria. The study-selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The diagnosis criteria for LBBB were based on the recommendations from the American Heart Association/American College of Cardiology Foundation/Heart Rhythm Society 20 in 4 studies 3,4,13,18 and from the World Health Organizational/International Society and Federation for Cardiology 21 in 2 studies. 11,19 One study 12 did not detail the diagnosis criteria. The study-selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…However, Urena et al and Testa et al reported no association between NOP-LBBB and HF admission. 13,19 This may be due to the uncertain permanency of NOP-LBBB.…”
Section: Permanent Pacemaker Implantation In New-onset Persistent Lefmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Smaller case series have demonstrated an increase in syncopal events and PPM insertion in patients with persistent LBBB and may be related to the progression of LBBB toward CHB described above. 22,23 Previously, TAVR has been shown to improve or maintain left ventricular function (LVF), especially among patients with baseline depressed ejection fraction. 24 In those with persistent LBBB, however, there is greater propensity for LV dyssynchrony and failure of LV ejection fraction to recover at one year.…”
Section: Significance Of Lbbbmentioning
confidence: 99%